Activation of diffusion during the formation of boride layers on the surface of steel parts - S. M. Usherenko; V. G. Dashkevich; Yu. S. Usherenko (Литьë и металлургия)
The features of structure formation of diffusion layers obtained by the technology, including preliminary surface treatment of steel products and subsequent thermal diffusion boriding in powder media, have been investigated. Pretreatment consisted in surface activation by superdeep penetration with a powder composition based on SiC of steel samples made of У8 steel. The features of the activation zones and their distribution over the surface are noted. The features of the activation zones and their quantitative characteristics are noted. A structural analysis of the obtained diffusion layers for the variants of low-temperature (650 °C) and high-temperature (920 °C) boration has been carried out. The chemical composition of the layer and the distribution of the main elements in it are analyzed. In both cases, a change in morphology was noted, consisting in the formation of a more compact diffusion layer and rounding of boride needles in the zone adjacent to the base metal. An increase in the layer thickness by 20–50 % and an increase in the proportion of the high-boron FeB phase relative to the variant of borating without preliminary activation were established.